Hydrodessus ducke sp. n. and new records of other species of the genus (Coleoptera, Dytiscidae, Bidessini) - Benetti, Cesar J.; Michat, Mariano C.; Hamada, Neusa (Zootaxa, 2020)
Hydrodessus ducke sp. n. is described and illustrated based on specimens collected in Amazonas State (northern Brazil), bringing the total number of Hydrodessus species to 33. The new species can be distinguished from other species in the genus by body size and shape, coloration, and characteristics of the elytral carina, prosternal process, metaventral carina, and male genitalia. The male of H. latotibialis Miller, 2016 is described and illustrated for the first time from specimens collected in Pará State, northern Brazil. New records for 17 species from Brazil, French Guiana and Suriname are provided, and the newest existing key to species is updated to accommodate the new taxon.